On my honor - Bauer, Marion Dane. (New York : Clarion Books, 1986)
When his best friend drowns while they are both swimming in a treacherous river that they had promised never to go near, Joel is devastated and terrified at having to tell both sets of parents the terrible consequences of their disobedience.
Elem. School Library Collection.
Wilson's Children.
Wilson's Junior High School.
Book Links (A.L.A.), February 2001.
Booklist, September 2004.
Elem. School Library Collection, June 2000.
Keywords: Accidents -- Fiction; Conduct of life -- Fiction; Friendship -- Fiction; Obedience -- Fiction; Accidents -- Fiction; Obedience -- Fiction